Theory and practice of Design Thinking: perspectives of designers and business consultants. Issue 3 (3rd July 2021) - Bongiovanni, Ivano; Louis, Cynthea Premala
ABSTRACT: The job of designers and business consultants features undeniable commonalities: focus on complex organizational problems, nearly constant exposure to ambiguity, difficulty in measuring performance and need to leverage knowledge and other intangible assets. Synergies between the disciplines of design and business consulting have increased in the last couple of decades. Design Thinking has emerged as an approach to solve business problems by thinking like a designer to leverage creativity and innovation. Despite its success, this has also raised some criticism: a diffused skepticism toward a public relation term that entails expensive invoices to simply apply old-fashioned creative thinking. What do the real protagonists think of Design Thinking and its application in the business world? We explored the perceptions of designers and business consultants on the theory and practice of Design Thinking. We interviewed 11 such professionals and our findings identified significant differences in perceptions around the essence, practicality and value of Design Thinking. Our research supports calls in the literature for establishing stronger connections between the principles of designerly thinking and the practice of Design Thinking in business.